Microscopic Stress Sensitivity Analysis with In Situ SEM Study and Digital Core Deformation Simulation - Weibo Sui; Yanan Hou; Zhilin Cheng (Geofluids)
Rock stress sensitivity is typically investigated macroscopically. In contrast, a new method combining in situ Scanning Electronic Microscope (SEM) study and digital core deformation simulation is developed in this paper, providing an effective way to investigate the relationship between microstructural deformation and decreasing permeability. The simulation method might replace in situ SEM study under certain scenarios. First, the in situ SEM study was implemented, and the microstructure deformations of rock samples during uniaxial loading were observed and recorded. The SEM images at different stress states were analyzed by digital image correlation (DIC) technique to investigate the principles of these deformations. A deformation simulation method was correspondingly proposed. The simulation effectiveness was demonstrated by comparing the simulation and the in situ SEM study results. To validate the simulation method for the three-dimensional (3D) digital core, porosity-permeability integrated measurements under triaxial stresses were conducted to obtain macroscale data under different stress states for a tight sandstone sample. A 3D digital core was reconstructed by micro-CT imaging with the same rock sample. Under the constraints of the measured porosity changes, the 3D digital core deformation was simulated. A series of simulated cores at different stress states were used for pore network model extraction, and the corresponding permeability was calculated. A comparison of the permeability changes of the simulation and porosity-permeability integrated measurements indicated consistently that the simulation method can characterize the 3D digital core stress sensitivity. In addition, the in situ SEM study results revealed that the throats deformed more severely than the pores by generating the pore and throat diameter frequency distributions at different stress states. Therefore, we concluded that throat deformation is more critical than pore deformation for permeability reduction.